PERFORMANS ITIK PEDAGING (LOKAL X PEI - Arianti Arianti; Arsyadi Ali (State Islamic University of Sultan Syarif Kasim Riau, 2009)
The study was conducted to determine the effect and maximum percentage of wa supplementation in diet on the peformance of starter duct meaty (Lokal X Peking). Sixty day old duck (OOP) cross breed Lokal X Peking were used in completely randomized design with four treatments and three replications. They were fed . comercial ration (Bus 602-crumble) with four level of water sUPleJnenlation at 0 (A), 10 (B), 20 (q and 30% (0) of the total weight of fation. Supplementation of water in ration hom 10 to 30% were not significantly (P>O.05) different for all treatments for feed intake, daily gain, feedlgain (conversion) and water consumption of starter duct meaty (Lokal X Peking). Nevertheless, supplemented with10% of water in ration result the best performance of starter duct meaty (Lokal X Peking).